Primary health care policy and vision for community pharmacy and pharmacists in Portugal - Nadine Ribeiro; Helder Mota-Filipe; Mara P. Guerreiro; Filipa A. Costa (Pharmacy Practice, 2020)
The central role of the Portuguese National Health Service (P-NHS) guarantees virtually free universal coverage. Key policy papers, such as the National Health Plan and the National Plan for Patient Safety have implications for pharmacists, including an engagement in medicines reconciliation. These primary health care reform, while not explicitly contemplating a role for pharmacists, offer opportunities for the involvement of primary care pharmacists in medicines management. Primary care pharmacists, who as employees of the P-NHS work closely with an interdisciplinary team, have launched a pilot service to manage polypharmacy in people living with multimorbidities, involving potential referral to community pharmacy. Full integration of community pharmacy into primary health care is challenging due to their nature as private providers, which implies the need for the recognition that public and private health sectors are mutually complementary and may maximize universal health coverage. The scope of practice of community pharmacies has been shifting to service provision, currently supported by law and in some cases, including the needle and syringe exchange program and generic substitution, remunerated. Key changes envisaged for the future of pharmacists and their integration in primary care comprise the development and establishment of clinical pharmacy as a specialization area, peer clinician recognition and better integration in primary care teams, including full access to clinical records. These key changes would enable pharmacists to apply their competence in medicines optimization for improved patient outcomes.